Exploring the Medicinal Potential of Glycosmis cyanocarpa (Rutaceae) - Ashrafi, Sania; Sathi , Mst Nowsad Zahan; Mina, Sadia Tasnim (Bangladesh Pharmaceutical Journal, 2026)
Glycosmis cyanocarpa (Blume) Spreng., a member of the Rutaceae family, is a small shrub or tree distributed across South and Southeast Asia. Phytochemical investigations have identified 23 secondary metabolites, including quinolone alkaloids, phenolic compounds, sulfur-containing amides, terpenoids, and sterols, many of which exhibit significant antimicrobial, antioxidant, cytotoxic and thrombolytic activities. Notably, novel sulfur-containing amides have demonstrated antifungal activity, while other isolated compounds have shown antioxidant and antimicrobial properties. The crude extract and its fractions also exhibited pharmacological properties, further supporting the therapeutic potential of G. cyanocarpa. Despite these promising findings, systematic studies on its bioactive constituents and pharmacological mechanisms remain scarce. This review consolidates the current knowledge on the phytochemistry and therapeutic potential of G. cyanocarpa, emphasizing its role as a source of bioactive compounds for drug discovery. While findings highlight its potential in therapeutic applications, further research is required to elucidate its pharmacological mechanisms and assess its viability for drug development. Bangladesh Pharmaceutical Journal 29(1): 99-106, 2026 (January)